PEMENTASAN TEATER SEBAGAI SUATU SISTEM PENANDAAN - Dede Pramayoza (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
This article aims to outline the essence of theatre performance as a signalling system from the perspective of theatre semiotics.The scope of the discussion in this article covers: (1) the components of the signalling system in theatre; (2) the changing ofsigns from the story to the stage; (3) the units of signs contained in the story and in the performance; and (4) how all the signsare joined together in a single system. Using a bibliographical study, each of these topics will be addressed and answeredinductively. Subsequently, through a descriptive analysis, the article will show which signs are involved in the manifestationof the script for the performance. It is hoped that this article will be useful for understanding that the meanings of a theatreperformance are essentially determined by the correlation of various units of signs that are involved in the process of signallingin the performance.Keywords: Theatre, Semiotics, System, Signalling